Stock return content analysis based on ratio method: Case study on infrastructure, utilities and transportation companies listed on IDX in 2018-2020 - Rahmawati, Sisca Dian; Putra, Febrianur Ibnu Fitroh Sukono (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
This research aims to analyze the effect of liquidity, leverage and profitability on the company's stock returns. Liquidity is proxied by current ratio, leverage is proxied by debt to equity ratio (DER), and profitability is proxied by return on assets (ROA). The research uses quantitative approach to explain the research purpose comprehensively through statistics scheme. The research population is all infrastructure, utility and transportation companies listed on Indonesian stock exchange in 2018-2020. This resesarch use purposive sampling technique and 27 companies as samples. The analysis method is classical assumption, multiple linier regression, hypothesis test, estimator model accuracy test and determination test. Several results show that liquidity, leverage, and profitability individually have significant effect on stock return. Based on the goodness of fit test shows liquidity with CR, leverage with DER and profitability with ROA simultaneously effect on stock return. The originality of this research is model initiation of the company's policy-making to increase stock returns in the future period through ratio analysis.